Bromatological and morphological characterization and yield of sugar cane top in Huasteca Potosina, Mexico - Ramírez-Cathí, H.; Salcedo, Aida C. C.; Briones, F.; Lucero, F. A.; Cárdenas, Alicia; Marcof, C.; Martínez, J. C. (Cuban Journal of Agricultural Science, 2016)
Morphological and bromatological composition was determined in four sugar cane varieties, burnt and green harvested. Three bunch were obtained per farms, belonging to 679 partners of the sugar mill “Plan de Ayala”. Bunch were weighed and quantified, separating stems from tops. The morphological evaluation was performed according to bunch weight, stem, sugar cane top, dry straw, green leaves, remaining top or apex. For the bromatological characterization, sugar cane tops were cut (5 mm cuts) and dried until reaching a constant weight between 90 and 95% of dry matter. The bromatological analysis determined dry matter, crude protein, ash, neutral detergent fiber, acid detergent fiber and in situ degradability. Variables were analyzed through a 4x2 factorial (four varieties and two harvests) in a completely random design. Varieties used were 02-CP72-2086, 03CO-997, 202MEX55-32 and 24MEX68-1366, and the harvests were green and burnt. Bunch production was different (P< 0.05). However, canes per bunch, stem percentage, tops and straws were not modified by variables. Likewise, factor harvest only affected (P<0.05) kilograms/bunch-1 and dry straw. General means of dry matter, crude protein, ash, neutral detergent fiber and acid detergent fiber were 93.1, 3.0, 5.9, 58.2 and 33.6%, respectively, without significant effect, due to the variety. General means for green and burnt sugar cane tops were similar to those of varieties with significant effect (P > 0.05), due to the harvesting method. It can be concluded that sugar cane top can be used as an input of ruminal feeding. Key words: nutritional quality, Saccharum officinarum, tropic